Investigation for Possible Association of the Topside and Bottomside Ionospheric Irregularities over the Midlatitude Ionosphere - Krishnendu Sekhar Paul; Haris Haralambous (Applied Sciences)
The present study investigates the characteristics of ionospheric irregularities at middle latitudes by examining the association between spread F (SF) events detected by Digisondes and medium-scale travelling ionospheric disturbances (MSTIDs) detected by GNSS with a special emphasis on the coupling with topside irregularities observed by Swarm satellites based on in situ electron density (Ne) measurements. We analyzed SF events over the European midlatitude region from 2015 to 2017, over six Digisonde stations coinciding with Swarm satellite overpasses. Swarm latitudinal Ne profiles were used to identify topside irregularities, while GNSS d-TEC and ROTI maps were used to track MSTIDs and irregularities, respectively. Based on ten selected cases demonstrating concurrent SF and topside irregularities, our findings suggest a strong association between SF in the bottomside ionosphere and fluctuations in topside Ne.